Association of Acute Myocardial Infarction with ankylosing Spondylitis: A nationwide longitudinal cohort study. (October 2018) - Park, Chong Jin; Choi, Yoon Jin; Kim, Jeong Gyun; Han, In-bo; Do Han, Kyung; Choi, Jung Min; Sohn, Seil
Highlights: A total of 12, 988 patients were enrolled in the AS group from January 1, 2010 to December 31, 2014. The control group consisted of 64, 940 subjects according to 1:5 age-sex stratified matching. 62 patients (0.48%) in the AS group and 157 persons (0.24%) in the control group developed AMI. The hazard ratio of AMI in the AS group was 1.81 (95% CI, 1.34–2.43) after adjusting for demographics and comorbid disorders. This is the largest and longest nationwide study to investigate increased risk of AMI in AS patients. Abstract: Pertaining to an association between Acute Myocardial Infarction (AMI) and Ankylosing Spondylitis (AS) is sparse. The purpose of this nationwide longitudinal study was to investigate the prevalence of AMI in newly diagnosed AS patients. A total of 12, 988 patients were enrolled in the AS group from January 1, 2010 to December 31, 2014 from the Korean National Health Insurance Service (NHIS). The control group consisted of 64, 940 subjects according to 1:5 age-sex stratified matching. The AMI incidence rates in AS and control group were compared using the Kaplan-Meier method. The hazard ratio of AMI and the control group was estimated by Cox proportional hazards regression analyses. During a 6 year follow up, 62 patients (0.48%) in the AS group and 157 persons (0.24%) in the control group developed AMI. The hazard ratio of AMI in the AS group was 1.99 (95% confidence interval [95% CI], 1.48–2.67) after adjusting for sex and age. The hazard ratio of AMI in the AS group was 1.81 (95% CI, 1.34–2.43) after adjusting for demographics and comorbid medical disorders. The incidence rate of AMI increases in newly diagnosed AS patients.